A Critical Review on the Book Hussain Ibn Musa (AS), His Life, Personality, Sepulcher - Mohammad Bagheri; Saeed Tavoosi Masroor (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Hussain ibn Musa ibn Jafar is a famous Alawi person who transmitted some Hadiths from his father Imam Musa al Kazim and his brother, Imam Ali ibn Musa al Rida (A.S). This lofty position and proximity to the Imamate line, caused the construction of some attributed Sepulchers to him in many cities, of which Tabas, located in the east of Iran, has more fame. Ali Akhavan Mahdavi has written a book on this important personality, his life, and his real place of burring. The present study aims to examine the book critically, therefore, tries to introduce and examine the book, then discusses some problems in it and presents suggestions regarding both the form and the content. So, we prepare our study with the use of a descriptive-analytical approach and of course a special usage of the main historical sources to which compare the contents of them. In conclusion, the author reached some important innovations in comparison with similar sources and studies, and it is completely clear by analyzing the content of hadith and genealogy books. Examination of the Akhavan Mahdavi's book showed that although this book has many advantages and has been effective on subsequent works written on this subject, but shortcomings such as lack of research background and critique of sources, the author's little use of Hadith and Rijal sources are among the cons. Some of the author's citations have diminished the book's credibility.